2010
DOI: 10.1055/s-0029-1240920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrapleural Povidone-Iodine Lavage on Thyroid Hormones in Thoracic Surgery

Abstract: The scores show that the iodine absorbed by the pleura during intraoperative povidone-iodine lavage has an effect on thyroid function. Intrapleural PI lavage results in changes to some thyroid hormone levels due to pleural absorption. Thus, intrapleural PI lavage should be used with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…showed that abdomens washed with 2% PI did not cause significant changes in TSH, thyroxine T3 and T4. Other studies have shown that pleural cavity irrigation, mediastinal irrigation, and iodine‐coated internal fixators do not cause thyroid dysfunction 24,25 . In addition, PI is considered to be a weak allergen, with its allergy incidence rate at only 0.4% 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that abdomens washed with 2% PI did not cause significant changes in TSH, thyroxine T3 and T4. Other studies have shown that pleural cavity irrigation, mediastinal irrigation, and iodine‐coated internal fixators do not cause thyroid dysfunction 24,25 . In addition, PI is considered to be a weak allergen, with its allergy incidence rate at only 0.4% 26 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that pleural cavity irrigation, mediastinal irrigation, and iodine-coated internal fixators do not cause thyroid dysfunction. 24,25 In addition, PI is considered to be a weak allergen, with its allergy incidence rate at only 0.4%. 26 In orthopedic clinical work, PI solution or PI diluted in normal saline are often used to irrigate the incision, which has been shown to have a good effect on preventing infection.…”
Section: Surgical Infection and Pi Irrigationmentioning
confidence: 99%
“…The washing operation has been repeated twice. At selected intervals (1,2,4,6,8,12,20 and 24 h) 1.5 ml of the dermal bathing solution was removed and collected for the analyses. Each receptor sample was immediately replaced with an equal volume of fresh made physiological solution.…”
Section: The Experimentsmentioning
confidence: 99%
“…In patients where the burned injury spread over 25% of the skin surface with deep second-and third-degree burns, the serum total iodine levels have been reported to markedly increase to 4500-48,000 mcg/dl and possible systemic complications due to elevated free iodine levels have been reported (Aiba et al, 1999). The amount of absorption is higher in cases of skin damage or the presence of thinner skin, therefore this effect was noted in infants (Erdogan et al, 2013;Findik et al, 2010). In animal experiments, transcutaneous absorption of PI through healthy skin has also been examined using radioisotope I125 (Furudate et al, 1997).…”
Section: Introductionmentioning
confidence: 99%